ELECTRONIC WORD OF MOUTH TERHADAP PURCHASE INTENTION PADA BRAND SEPATU BATA YANG DIMEDIASI DENGAN BRAND IMAGE : PERSPEKTIF THEORY OF PLANNED BEHAVIOR - Astina, Mutiara Andin; Wibisono, Dimas (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This research aims to determine the influence of electronic word of mouth on purchase intention for the Bata shoe brand which is mediated by the brand image perspective of the theory of planned behavior. This research uses primary data obtained from questionnaires with a quantitative approach. The data analysis technique used is multiple linear regression analysis with the SmartPLS 3.0 analysis tool. This research uses a non-probability sampling technique using purposive sampling. This technique is used because this research has certain criteria. The data used in this research are electronic word of mouth, brand image, and purchase intention. The research results show that electronic word of mouth has a positive and significant effect on purchase intention, the influence of electronic word of mouth has a positive and significant effect on brand image and brand image has a positive and significant effect on purchase intention, and at the same time brand image has a positive and significant effect in mediating electronic word of mouth on purchase intention.